Chinese Burn Surgery - Yang, Zongcheng (Springer Netherlands : Imprint: Springer, 2015)
This is a comprehensive book in burn surgery, written by 25 experts in China. It summarizes the theoretical basis of and clinical experience in the prevention and control of burn injuries. It is a comprehensive and up-to-date reference book for surgeons and scientists working with burn management. The different degree of burns and surgical techniques during burn wound care, reconstruction and healing are reviewed separately. Authors also introduce successful cases in different kinds of burns.   Editor Zongcheng Yang is a professor at Southwest Hospital, Third Military Medical University, Chongqing, China.